Unidade, diversidade e a invenção dos índios: entre Gabriel Soares de Sousa e Francisco Varnhagen - Monteiro, John Manuel (Revista de História, 2003)
This article analizes Gabriel Soares de Sousa's description of Indians in two distinct contexts: that of the period in which he wrote his work (1580s) and that of the period in which the first complete edition was published by F.A. Varnhagen (mid-nineteenth century). The author seeks to show how Sousa's detailed descriptions and schematic classifications became incorporated as ethnographic facts by the first generation of historians in Brazil after it became a nation.